MENEGUHKAN AKHLAK QUR'ANI DI TENGAH GURITA DIGITAL: RESISTENSI SANTRI ATH THOHIRIYYAH BANYUMAS TERHADAP DEGRADASI MORAL - Arifah Choirun Nisa; Uswatun Hasanah; Lisnawati; M. Misbah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research delves deeply into the cultural resistance strategy developed by the students of the Ath Thohiriyyah Banyumas Islamic Boarding School in maintaining Qur'anic morals in the midst of the onslaught of the digital era. Through a critical ethnographic approach for nine months, this study reveals how students knit moral defense fortresses by activating their cultural, spiritual, and social capital. The findings of the study show that resistance is not carried out confrontationally, but rather through subtle practices such as value encapsulation, cultural hybridization, and identity affirmation. The